Optimazing the abandon mining as an alternative for tourism destination: the case of Lombok Island. (January 2020) - Agustriani, E; Anggraeni, J D; Ang, M; Kusnadi,; Pratiwi, Y
Abstract: The environmental impact of mining on land is unavoidable, which calls for actions to optimize the unused surface-mined lands. One of the alternatives is to the unused surface-mined lands for tourism destinations. As a tourism destination, this effort will local people in terms of regional development and community's incomes. This research aims to analyze the extent of how to utilize the unused surface-mined lands in the Balibe Hill, Bonder Village, Central Lombok. The research design will employ field observation and interviews with local government and local community. This is important to gain data and information about the existing environmental condition and the community's livelihood in the study location. The data will be analyze to find out the possibility of turning the unused surface-mined lands into tourism destinations and assessing the benefits of the initiative on the environment and the local community. The results show that the alternative use of the unused surface-mined lands can be beneficial if they are designed to become tourism destinations. Unproductive lands can be converted into productive lands, considering that tourisst destination in the unused surface-mined lands will have specific and unique identity for tourists. The new tourist destination requires facilities and infrastructure that are representative to support the functions.